The role of Islamic Institutions as B40 aid centre in Sabah - Dayangku Aslinah Abd. Rahim; Siti Hajar Samsu; Lim, Beatrice Fui Yee; Roslinah Mahmud; Khairul Hanim Pazim (Academic Inspired Network, 2022)
One of the Malaysian government's initial efforts to curb the spread of Covid-19 in the country is through the implementation of the movement control order, where many economic sectors had to be closed through various stages and phases. The cessation of operations and the restriction of the movement have caused many people to lose their jobs and sources of income, including the poor and needy. Thus, this study aims to explore the role of Islamic institutions and finance such as mosques, zakat and baitulmal in Sabah to help the affected group of Covid-19 especially B40 from an Islamic perspective. The methodology of this study is through library research, current data analysis, selection of relevant information and recommendations on the role of the mosque as a one-stop aid center in Sabah. The results of the study found that zakat, baitulmal and mosques are among the Islamic institutions that are active in helping the poor in Sabah. Zakat institutions, for example, emphasizes on four main roles in helping those affected by the pandemic in Sabah. Meanwhile, the Baitulmal institution functions as a complement to the zakat institution in aiding and alms to the community. It was found that the baitulmal collection obtained from various sources such as fidyah, donation, fines, and atonement for violators of Islamic law are very useful to help those affected during the Covid-19 pandemic in Sabah. In addition, mosques are seen to be active in donating cash and goods to those affected by the pandemic. Apparently, the Covid-19 epidemic has placed the role of Islamic financial institutions at a significant level in the economic system in Sabah, especially to the affected groups such as B40. Finally, this paper has suggested that the mosque can be strengthened as a one-stop aid center that is actively helping the B40 group, especially in Sabah.